In vitro Assessment of the Impacts of Leaflet Design on the Hemodynamic Characteristics of ePTFE Pulmonary Prosthetic Valves - Zhu, Guangyu; Wei, Yuan; Yuan, Qi; Cai, Li; Nakao, Masakazu; Yeo, Joon Hock (Frontiers in Bioengineering and Biotechnology, 2020)
Surgical pulmonary valve replacement (PVR) is one of the most common approaches in the management of patients with congenital heart disease. The discouraging long term outcomes of standard prostheses for PVR, including homografts and bioprosthetic, constrained their indications. Recent developments in the expanded-polytetrafluoroethylene (ePTFE) pulmonary prosthetic valves provide promising alternatives. In this study, the hemodynamic characteristics of bileaflet and trileaflet ePFET valve designs were experimentally evaluated. The in-vitro tests were performed under the right ventricle (RV) flow conditions by using an in-vitro RV circulatory system and particle image velocimetry (PIV). The leaflet kinetics, transvalvular pressure gradients, effective orifice areas, regurgitant fractions, energy losses, velocity fields and Reynolds shear stress (RSS) in both prostheses were evaluated. The opening of the bileaflet and trileaflet valve cost 0.060 s and 0.088 s, respectively. The closing of the former takes 0.140 s, in contrast to 0.176 s of the latter. The trans-valvular pressure is 6.8 mmHg in the bileaflet valve vs. 7.9 mmHg in the trileaflet valve. The effective orifice area is 1.83 cm2 in bileaflet valve and 1.72 cm2 in bileaflet valve. The regurgitant fraction and energy loss of bileaflet are 7.13% an 82 mJ, which are 7.84% and 101.64 mJ in its bileaflet counterpart. The maximum RSS of 48.0 Pa and 49.2 Pa occur at the systole peak in bileaflet and trileaflet valve, respectively. A higher average RSS level is found in the bileaflet valve. The results form this preliminary study indicates that the current bileaflet prosthetic valve design is capable of providing a better overall hemodynamic performance than the trileaflet design.